O analiză critică asupra dezvoltării agriculturii și zonelor rurale, pe baza PNDR 2007-2013 - Mihalache, Flavius (Calitatea Vieții, 2013)
The Romanian rural areas are facing three major problems: underdevelopment of the non-agricultural activities in the rural economy; widespread of the traditional agriculture and the low level of productivity of the rural activities; underdevelopment of most of the rural communities. The Romanian strategy for Rural Development is based on National Rural Development Programme (NRDP). In the period 2007–2013 Romania has a budget of 10 billion euros for financing the agricultural sector and the rural development programs. This article is focused on the analysis of the financial intervention in the Romanian rural areas, through NRDP policy, as part of the European Common Agricultural Policy (CAP). The paper has two main objectives: to explore the main problems NPRD occurs and to discuss about its matching to the socio-economic reality of Romania. This paper consists in a desk-research, using secondary analysis on statistical reports and official documents as the methodological background. In this way, the main data sources for the analyses are: Ministry of Agriculture and Rural Development, Interim report of National Rural Development Programme (2011); Ministry of Agriculture and Rural Development – General Directorate for Rural Development, The situation of the NPRD projects, recorded in monitoring tables on the date of March 21, 2013; The National Rural Development Programme 2007–2013 (consolidated version, December, 2012). Available data show important differences among NRDP measures: some of them have a good situation, but parts of them are delayed. In the same time, we observed some important differences between the coordinates of National Program for Rural Development and the coordinates of the rural areas. This aspect seems to be a very difficult one. Our findings, in line with previous studies, show that there is not a perfect match between the financial support programmed and the Romanian rural reality. To maximize the impact of the support, Romanian authorities have to reconsider some aspects of the financial schemes for the next period of intervention: 2014–2020.